Magnetic domain wall depinning assisted by spin wave bursts - Woo, Seonghoon; Delaney, Tristan; Beach, Geoffrey S. D. (NATURE PUBLISHING GROUP, 2017)
Spin waves (SWs) in magnetic structures could potentially be exploited for high-speed, low-power magnonic devices for signal transmission(1-4) and magnetic logic(5-9) applications. The short wavelengths and high frequencies of dipole-exchange-mode SWs in metallic ferromagnets make them particularly suitable for nanoscale devices(10-14). However, these same characteristics make generation and detection challenging due to the length-scale mismatch of conventional SW interfaces such as microwave striplines. Here we show numerically and experimentally that colliding domain walls (DWs) release energetic spin wave bursts that can couple to and assist depinning of nearby DWs. Hence, DWs can be used as stationary reservoirs of exchange energy that can be effciently generated, manipulated, and used to release SWs on demand, which can subsequently be detected again using DWs. This work highlights a route towards integrating DWs and SWs for enhanced functionality in spintronics applications.
Keywords: LOGIC